Legal and Political Implications of Designating the Free Papua Movement as a Terrorist Organization - Ridarson Galingging (International Journal of Business, Economics, and Social Development, 2023)
This article examines what the legal and political implications are of the recent Indonesian government’s decision of designating the Free Papua Movement (OPM) as a terrorist organization. For that purpose, armed separatism in West Papua will be explained and then followed by an elaboration of the threat of terrorism in Indonesia and a discussion of the labelling of OPM as a terrorist organization. The terrorist designation of the OPM will apply the Indonesian anti-terrorism law that gives longer pre-trial detention power to the Police and the possibility of placing OPM on the terrorist list. The Indonesian government seems to gain political support from the Muslim community that has criticized the government for using the terrorism issue against Islam only before the designation was announced. The method and approaches used in this work are grounded in descriptive as well as normative judicial analysis.